Level of physical activity among adolescents in a district of the callao region - Morales Quispe, Juan (2016)
o determine the level of physical activity (PA) and the association of this factor with excessive Internet use among adolescents from the "Mi Perú" district in the Callao region. Materials and Methods. This cross-sectional descriptive study included 15-19-year-old students at state schools in the "Mi Perú" district. The long version of the Physical Activity Questionnaire (IPAQ) was applied in the subjects’ classrooms between October and December 2013. PA was expressed in metabolic equivalent of task (MET) units and classified as low, moderate, and high. Internet usage of ≥20 hours per week was considered excessive. Results. Of the total participants, 59% (272), 25.8% (119), and 15.2% (70) had high, moderate, and low levels of PA, and 50% of adolescents had a PA level ≤4,212 MET/min/wk. According to the IPAQ, higher levels of PA were achieved in the areas of "house work" and "recreation". The PA for house work was higher in female subjects relative to male subjects (p=0.010), whereas the PA for recreation was higher among male subjects (p=0.009). Only 2.6% (12) of teenagers used the Internet for >20 hours per week. Conclusions. This study reveals a high level of PA and a lack of association between the PA level and excessive Internet use in the studied population.